Moderation of Social Media Marketing on the Influence of Price on Purchase Decision - Subrata, I Made Subrata; Dewi, Luh Komang Candra Dewi; rimanta, I Made Rimanta (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to analyze the Moderation of Social Media Marketing on the Influence of Price on Purchasing Decisions (Case Study at The Coffee Club Hotel Anantara Vacation Club Legian). The population in this study were all consumers of The Coffee Club Hotel Anantara Vacation Club Legian. The number of samples used was 100 consumers. The research analysis technique used validity test, reliability test, and PLS analysis. The results of the analysis show that 1) price has a positive effect on social media marketing; 2) price has a positive effect on purchasing decisions; and 3) social media marketing is able to moderate the influence of price on purchasing decisions of The Coffee Club Hotel Anantara Vacation Club Legian. Suggestions in this study are expected that The Coffee Club Hotel Anantara Vacation Club Legian can offer various prices for different consumer segments, can provide content that highlights aspects of Balinese culture and local experiences that can be enjoyed around the hotel, and can be done by offering a more diverse menu variety and in accordance with local and international preferences.  Keywords: Pricing, Social Media Marketing, Purchasing Decision